KEADILAN DALAM PEMIKIRAN ASGHAR ALI ENGINEER DAN RELEVANSINYA DENGAN NILAI-NILAI PANCASILA DI INDONESIA - Wahyu Isman Asmi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
AbstractThis paper is a study of the law, especially those related to the concept of justice. Justice as it is known is an important component in human life. Everyone must uphold the value of justice so that there is no longer any form of oppression and unequal treatment between one another. One of the thoughts of Islamic leaders studied in this study is Aghar Ali Engineer. Justice in Ali Engineer's opinion is one of the important aspects or needs for every human being to be able to balance between demanding his rights and carrying out the obligations that should be carried out. A law that does not carry out justice properly is only a theory if it cannot be practiced or applied in state life. This research is also relevant to the values of Pancasila, especially the fifth principle, namely social justice for all Indonesian people. Justice in Ali Engineer's thinking is in line with the principle of justice in the Pancasila precepts in Indonesia. This research is library research using primary sources from the work of Ali Engineer and also referring to secondary sources as supporters